Aplicação de testes hemostáticos na avaliação do risco trombótico em cadelas com carcinoma mamário - Trentin, Thays de Campos [UNESP] (2014)
Mammary tumuor are considered the most common tumors in dogs and can often predispose these animals to hemostatic complications secondary to neoplasia. In this context, thrombosis is a major hemostatic abnormality in patients with cancer, that is often discovered late. Hemostatic tests have been used in human medicine for an earlier diagnosis, allowing a better prognosis of neoplastic conditions. However, in dogs with cancer tests to diagnose hypercoagulable states are rarely used. In veterinary medicine the correlation between cancer and hypercoagulability has been a constant finding in dogs, but most of the times, unlike human medicine, it is devoided of clear clinical signs. The need for hemostatic evaluation to establish a better treatment protocol and prognosis in different types of cancer is evident in these patients. Aiming to evaluate the hemostatic profile and the possible hypercoagulable states in dogs with mammary carcinoma, 30 female dogs were selected, 15 healthy female (control group) and 15 females dogs with breast carcinoma confirmed by cytology and histopathology. Both groups were submitted to underwent hemostatic evaluation by the tromboelastrometry (INTEM, EXTEM, FIBTEM), platelet aggregation, PT and aPTT. The results collected, were submitted to descriptive analysis, and then the means between groups was compared by the t test at the level p<0,01 and p<0,05. The results, showed significant differences in hemostatic routine tests resulting in increased platelet aggregability and TP. Thromboelastometry had demonstrated a significant reduction in CT (EXTEM, FIBTEM), CFT (INTEM, EXTEM), and ML (INTEM, EXTEM) and an elevation in α angle (INTEM, EXTEM) and MCF (INTEM, EXTEM). It is concluded that dogs with mammary carcinoma present a higher thrombotic state risk associated to a hipergoagulable state